Kemampuan guru bahasa dalam merancang media evaluasi pembelajaran online - Nova Yulia; Ulfia Rahmi; Meira Anggia Putri (ABDI HUMANIORA: Jurnal Pengabdian Masyarakat Bidang Humaniora, 2022)
Online learning has been implemented widely at school, including in language learning. But, there are still many language teachers who encounter difficulties in doing online learning evaluations. To improve the language teachers' ability to do the learning evaluation with online media, we conducted training for the teachers about online learning evaluation media. Training participants were a group of Senior High School and Vocational high school teachers in Padang. The training was carried out with the stages of introducing the types of online learning evaluation media, tutorials on how to use some applications for online learning evaluation, and teachers simulating the online learning evaluation they had designed. The training result showed the improvement in teachers' ability to do learning evaluations with online media. The post-test results were two times higher than the pre-test results. Both tests' results showed a significant difference between before and after training.